Self-activatable carbon nanotube@ruthenium-catechol coordination complex for hydrogen evolution reaction. (1st October 2022) - Wu, Chenzhi; Wu, Tong; Tang, Zhenbin; Dai, Juguo; Zeng, Birong; Xu, Yiting; Chen, Guorong; Luo, Weiang; Yuan, Conghui; Dai, Lizong
Abstract: We report a simple metal ion-catechol coordination strategy to coat ruthenium-catechol polymer complex (TAC-Ru) on the surface of carbon nanotubes (CNT) to form a core–shell structure (abbreviated as CNT@TAC-Ru). This is achieved by firstly polymerizing catechol and boronic acid monomers on the surface of CNT to form a boronate ester polymer (BP) shell. Then, Ru 3+ is used to etch the BP shell, and cleave the dynamic boronate ester bond, leading to the formation of a CNT@ruthenium-catechol coordination complex based on the coordinative efficiency of the catechol group. The electrocatalytic property of the CNT@TAC-Ru composite can be activated through electrochemical cycling treatment. The as-activated CNT@TAC-Ru exhibits evidently improved hydrogen evolution reaction (HER) performance with an overpotential of 10 mV in 1.0 M KOH at a current density of 10 mA cm −2, which is better than that of commercial Pt/C (32 mV). And the long-term stability is also desirable. This work provides a pyrolysis-free method to form metal-polymer-carbon composite with high HER performance under the alkaline condition.